Kreativitas Wedha’s Pop Art Portrait - Yosi Samsul Maarif (PANTUN, 2019)
WPAP existence or Wedha Pop Art Portrait is now a role model new fl ow fan in art, especially the fi eld of fi ne arts in Indonesia. Community of fans and followers WPAP illustration style more and more, the role of computer graphics helped it easier for people to learn and make this pop art works. In making the work of a person is not prosecuted WPAP adept at drawing, because the source stems from the photo-tracing process then do faceting-coloring, then the picture is processed through Digital Imaging will change into a new form, especially in skin coloring, but still retaining the essence of the object. WPAP is a result of the creativity in the fi eld of art developed by modern artists Indonesia Wedha Abdul Rashid. This paper provides background on the study of the creation and the journey of creativity Wedha as the inventor WPAP style. The method used is descriptive analytical data collection techniques acquired through the study of literature and data from the electronic media. The fi nal result is a recommendation examples WPAP use in some media and event alerts and the Asian-African Conference in Bandung. Keywords: Wedha pop art portrait, digital imaging, Wedha’s creativity